Edukasi Peran Sarapan Pagi Dalam Meningkatkan Kinerja Akademik Mahasiswa - Elfi, Wa Ode; Pini, Citra Nurhalizah; Fazali, Lian Eka; Dani, Yuliah; Mahmud, Idham; Sakalo, Nevida; Effendy, Devi Savitri; Muchtar, Febriana; Tosepu, Ramadhan; Lestari, Hariati; Harleli, Harleli (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2024)
Breakfast plays a significant role in enhancing the academic performance of students, as it can affect concentration, memory, and mental health. Research shows that students who regularly have breakfast tend to have better levels of concentration and memory compared to those who skip breakfast, as well as experiencing lower levels of stress and anxiety. Education about the importance of a healthy breakfast is key to raising student awareness, and the use of educational media such as videos has proven effective in conveying information and motivating behavioral changes. Therefore, educational institutions are advised to provide healthy breakfast facilities and implement ongoing educational programs to support students in adopting good breakfast habits to improve their academic performance.